Expression of Proteinase-Activated Receptor 2 During Colon Volvulus in the Horse - Lambertini, Carlotta; Zannoni, Augusta; Romagnoli, Noemi; Bombardi, Cristiano; Morini, Maria; Dondi, Francesco; Bernardini, Chiara; Forni, Monica; Rinnovati, Riccardo; Spadari, Alessandro (Frontiers in Veterinary Science, 2020)
Large colon volvulus in horses is associated with a poor prognosis, especially when ischemic-reperfusion injury of the affected intestinal tract develops. Proteinase-activated receptor 2 (PAR2) plays an important role in the pathogenesis of inflammation in the gastrointestinal tract. The aim of this study was to evaluate the distribution and expression of PAR2 in colonic pelvic flexure of horses spontaneously affected by large colon volvulus (CVH group). Eight horses admitted for severe abdominal colon volvolus and which underwent surgery were included. Colon samples were collected after enterotomy. Data previously obtained from healthy horses were used as a control group. Histologic evaluation was carried out to grade the severity of the colon lesions. Immunofluorescence, western blot and quantitative polymerase chain reaction (RT-qPCR ) were carried out on colon samples to evaluate PAR2 expression. In addition, the transcriptional profile of cytokines and chemokines was evaluated using RT2 Profiler™PCR Array Horse Cytokines & Chemokines. Three out of the eight patients were euthanised due to clinical deterioration. Immunostaining for PAR2 was observed in the enterocytes, intestinal glands and neurons of the submucosal and myenteric plexi. In the CVH horses, the expression of PAR2 mesenger RNA (mRNA) did not differ significantly from that of the healthy animals; western blots of the mucosa of the colon tracts showed a clear band of the expected molecular weight for PAR2 (approximately 44 kDa) and a band smaller than the expected molecular weight for PAR2 (25kDa), suggesting its activation. The gene expressions for C-X-C motif ligand 1 (CXCL1); interleukin 8 (IL8), macrophage inflammatory protein 2 beta (MIP-2BETA) were upregulated in the colic horses as compared with the colons of the healthy horses. Therefore, in the present study, the expression and activation of PAR2 in the colons of horses in the presence of an inflammatory reaction like that occurring in those with spontaneous colon volvulus was confirmed.